(untitled) - Lewis, Richard J. (New York, 2000)
This handy, compact, easy-to-use pocket guide to the most frequently encountered hazardous materials is now significantly updated and revised, providing safety managers and workers with critical data and safety profiles for more than 750 chemicals in the millennium workplace. Each entry is carefully selected for its dangerous properties, reflecting current scientific findings as well as regulatory standards and safety and control recommendations. Clear, accurate descriptions for each substance let you assess its health and safety hazards quickly and easily.
Keywords: Hazardous substances,Industrial safety,Vật liệu nguy hiểm,An toàn công nghiệp